Neonatal cranial bone depression - Tenente, Joana; Cardoso, Ivana; Vinhas da Silva, António; Torres, Jacinto (BIRTH AND GROWTH MEDICAL JOURNAL, 2021)
A female preterm was admitted to the Neonatal Intensive Care Unit for late prematurity and very low weight. The physical examination was normal. On the third day of life, a hard left, non-painful parietal depression was noted, with no evidence of neurological impairment. Head computed tomography (CT) showed focal sinking of the left parietal bone posteriorly to the coronal suture. A watchful attitude was adopted and the patient was discharged on day 28. The diagnosis was a “ping-pong fracture”, which can occur iatrogenically or spontaneously in uterus. This diagnosis can be confirmed by x-ray or CT scan and the prognosis is usually good, with complete deformity regression. At two months, the parietal fracture was barely perceptible, and neurological examination was normal.